Pertumbuhan dan Hasil Tiga Varietas Alfalfa (Medicago sativa L.) dengan Perlakuan Tiga Macam Rhizobium pada Media Tanam Regosol Asal Banguntapan - Renan Subantor, Prapto Yudono, dan Bambang Suwignyo (Jurnal Ilmu Pertanian, 2012)
ABSTRACTDifferent alfalfa varieties type of Rhizobium (a side of Rhizobium meliloti) affect to root nodule formation that will have an influence on the growth and yield quality of alfalfa. The rare presence of Rhizobium meliloti so it need to look for other potential rhizobium  expected  to  form  root  nodules  of  alfalfa.  The purpose  of  this research is to study  the interaction of  the three varieties of  alfalfa inoculated with different type of rhizobium on growth and quality of alfalfa yield of the first cut.The experiment was conducted using a completely randomized design with factorial experiment in March to June 2012 in the Green House Laboratory of Forage and Pasture Feed Faculty of Animal Husbandry Gadjah Mada University. Data measurements and observations were done on growth parameters and the quality of the results and were analyzed by analysis of variance with a completely randomized design, and followed by Duncan's multiple range test level 5%. Regression correlation analysis performed to determine the relationship between two variables to determine the effect of growth and quality of alfalfa yield.The results showed that various rhizobium inoculated on Multiking 1, Vernal and Common failed and the unable to form viable root nodules. Several physiological   parameters such as growth and photosynthetic rate, net assimilation rate and relative growth rate, showed significant differences between the combination treatment. Generally indicates that all combinations of treatments have relatively high levels of khlorofil, value between 1 to 3.3. Quality nutrients such as crude protein, crude fat, crude fiber, ash content and energy digestibility Variety Multiking 1, Vernal and Common are not significantly different. Nutritional quality and in vitro digestibility of Multiking1, Vernaland Common are not significantly different.Keywords: alfalfa varieties, type of rhizobium, growth, quality of yield, and in vitro digestibility